Obesity Does Not Increase Complication Rate of Percutaneous Epicardial Access. (18th August 2014) - WAN, SIU‐HIN; KILLU, AMMAR M.; HODGE, DAVID O.; PACKER, DOUGLAS L.; MULPURU, SIVA; ASIRVATHAM, SAMUEL J.; MUNGER, THOMAS M.; FRIEDMAN, PAUL A.
Epicardial Access and Obesity Introduction Percutaneous epicardial access for ablative therapies is an increasingly common technique utilized for refractory ventricular arrhythmias. There are, however few known data on obesity and complication rates associated with this procedure. Methods and Results We retrospectively reviewed the charts of subjects undergoing epicardial access at Mayo Clinic between January 2004 and June 2013. Baseline clinical and echocardiographic data were collected for each subject, who was then classified into body mass index (BMI) categories as underweight, normal weight, overweight, and obese based on a BMI of <18.5, 18.5–24.99, 25–29.99, and ≥30, respectively. Events and complications were recorded, and procedural and clinical success rates were determined. There was no statistically significant difference in access approach, procedural or clinical outcomes, or complications among the BMI categories. Note that 95.1%, 91.7%, and 93.1% derived procedural success among the normal weight, overweight, and obese categories, respectively (P value = 0.81). Similarly, there was no difference in clinical outcomes with success rates of 68.3%, 66.7%, and 75.9% between the respective groups (P value = 0.54). At 5 years, there was a trend toward increased mortality among obese individuals (28.8%) compared to normal weight (8.8%) and overweight (9.8%) patients (P value = 0.139). Conclusion Percutaneous epicardial access, mapping, and ablation can be performed in obese individuals with similar outcomes to those of lower weight category. Obesity should not preclude the use of percutaneous epicardial access when clinically indicated.